The Views of Islamic Business Ethics on Printing Business Competition - Mustika, Mega Ariyani; Munip, Al (Zabags International Journal of Economy, 2024)
In this study, the researcher focused on competition in the printing business from the perspective of Islamic business ethics. The data analysis method used in this research is descriptive analysis. This research aims to identify business competition in the effectiveness of Islamic business ethics applied by printing business owners. Participants in this research are owners, employees and customers. In obtaining data in the field, observation, interviews and documentation are used. The results of the research obtained are: Business Competition in the Perspective of Islamic Business Ethics is going well even though the printing business owners in Talang Babat are not very knowledgeable in religious knowledge, but they believe that the business they run is in accordance with Islamic teachings and does not harm the printing business, they compete. in a healthy manner and not tearing each other down.